Analysis of Minichromosome Maintenance-2 (MCM-2) and Cyclin D1 Expression in Meningioma - Kurniawati, Yuliana; Fauziah, Dyah (Folia Medica Indonesiana, 2018)
World Health Organization histopathological grading of meningioma is associated with recurrence and clinical outcome. Grade II meningioma can be difficult to distinguish with grade I especially in case in which mitosis is not easily identified. MCM-2 and Cyclin D1 play crucial role in cell cycle and have been reported overexpressed in many malignant tumors. The aim of this observational analytic study was to analyze the differences and correlation between MCM-2 and Cyclin D1 in various meningioma grading. Immunohistochemystry with MCM-2 and Cyclin D1 was performed on 25 paraffin blocks of grade I, II and III meningiomas at the Laboratory of Anatomical Pathology, Dr. Soetomo Hospital. The immunoexpression are evaluated using Labelling Index, then analyzed statistically. The results showed significant difference in expression of MCM-2 within various meningioma grading (p=0.000) and significant difference in expression of Cyclin D1 within grade I and II also within grade I and III (p<0.050), but not in grade II and III (p>0.050). There was also positive correlation between MCM-2 and Cyclin D1 expression in various meningioma grading (rs=0.683, p=0.000). MCM-2 may play role in distinguishing various meningioma grading. Cyclin D1 can distinguish grade I and II also grade I and III, but not grade II and III. Overexpression MCM-2 was along with Cyclin D1 in various meningioma gradings.